Additional description of karyotype and meiotic features of Takydromus sexlineatus (Squamata, Lacertidae) from northeastern Thailand - Isara Patawang (2018)
© 2018, Archana Sharma Foundation of Calcutta. This study determined the standardized karyotype and idiogram of Takydromus sexlineatus from Surin Province in northeastern Thailand. Mitotic metaphase chromosomes from bone marrow cells and different meiotic stage from testicular cells respectively were studied after staining with conventional Giemsa and Ag-NOR banding techniques for chromosome identification. The study was carried out with samples taken from both male and female T. sexlineatus, the sex of which was identified by external examination. The results showed that the diploid chromosome number of T. sexlineatus was 2n = 38 and the fundamental number (NF) was 38 in both male and female. Although chromosome study was done in both sexes of T. sexlineatus, this study does not identify the sex chromosomes. This is because of the limitation of the staining techniques used. Therefore, we did not conclude on the sex chromosome system in this species and all chromosomes were taken as autosomes. The types of autosomes observed were 16 large telocentric, 14 medium telocentric, and 6 small telocentric macrochromosomes and 2 microchromosomes. Our result is the new record in Thailand on this species and NOR characteristics by silver staining is the first report on NOR banding in this species. The karyotype formula of T. sexlineatus thus was found as: 2n(38) = L16t+ M14t+ S6t+ 2 microchromosomes.